Group portrait of the attendees of the 1950 California Conference Institute Toyon #1 - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the California Conference Institute Toyon #1 meeting, held June 20-27, 1950 at Monte Toyon in Aptos, California. Some of the attendees can be seen holding signs and banners that read: "Santa Clara, " "Sebastopol," "Hollister" and "Crusaders."